The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/j.eurpsy.2003.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences and outcome in schizophrenia: a 2-year follow-up study in a large community sample

Abstract: This study examined gender differences in the short-term (2 years) course of schizophrenia in a sample of 200 schizophrenic (DSM-IV criteria) outpatients (74 women and 126 men). Number and length of hospitalizations during the prospective follow-up were recorded. After 2 years, men were found to have more hospitalizations and longer stays than women. Among subjects who had at least one hospitalization (12 women and 38 men), men had greater length of hospitalization. In conclusion, schizophrenic women had a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
24
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 7 publications
9
24
1
Order By: Relevance
“…Although the observed differences in symptoms and functioning did not remain significant after Bonferroni correction for multiple comparisons, they were exactly as predicted a priori, and they support the large literature in the field indicating that there are differences in the clinical presentation of male and female participants with psychotic disorders (Angermeyer, Kühn, & Goldstein, 1990;Bardenstein & McGlashan, 1990;DeLisi et al, 1989;Goldstein & Link, 1988;Grossman et al, 2006;Hambrecht et al, 1992;Lindamer et al, 2003;Shtasel et al, 1992;Usall et al, 2003). These findings suggest that underlying differences may predate the onset of psychosis.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although the observed differences in symptoms and functioning did not remain significant after Bonferroni correction for multiple comparisons, they were exactly as predicted a priori, and they support the large literature in the field indicating that there are differences in the clinical presentation of male and female participants with psychotic disorders (Angermeyer, Kühn, & Goldstein, 1990;Bardenstein & McGlashan, 1990;DeLisi et al, 1989;Goldstein & Link, 1988;Grossman et al, 2006;Hambrecht et al, 1992;Lindamer et al, 2003;Shtasel et al, 1992;Usall et al, 2003). These findings suggest that underlying differences may predate the onset of psychosis.…”
Section: Discussionsupporting
confidence: 75%
“…Studies have consistently shown there are gender differences in age of onset, severity of negative symptoms, long-term functioning and social support for patients with schizophrenia (Angermeyer, Kühn, & Goldstein, 1990;Bardenstein & McGlashan, 1990;DeLisi et al, 1989;Goldstein & Link, 1988;Grossman et al, 2006;Hambrecht et al,1992;Lindamer et al, 2003;Shtasel et al, 1992;Usall et al, 2003). Some of these differences have also been observed in individuals with schizotypal personality disorder and other schizophrenia spectrum disorders Gurrera et al, 2005).…”
Section: Introductionmentioning
confidence: 89%
“…Certain predictors (education, 'living with parents' and 'contact with friends') were more specifi c for females while others were more valid for males ('the highest GAF the year before admission' and 'current GAF'). Although it is well known that females more often have a better pre-morbid functioning than males (Foerster et al, 1991;Hafner, 2003;Lindamer et al, 2003;Preston et al, 2002;Salokangas et al, 2003;Usall et al, 2003) it was somewhat unexpected that the highest GAF the year before admission did not contribute to explaining outcome among females being the strongest predictor among males. Previous studies have shown that the level of functioning before onset together with DUP have been the two most important predictors for poor outcome (Drake et al, 2000;Harrigan et al, 2003;Larsen et al, 2000;Malla et al, 2002;Marshall et al, 2005;McGorry et al, 2000;Norman et al, 2005;Perkins et al, 2005).…”
Section: Discussionmentioning
confidence: 68%
“…The PRS showed promising results in assessing those at a risk of an unfavourable outcome (Flyckt et al, 2006). It is well known that males and females differ regarding age at onset, clinical features and outcome of psychosis (Foerster et al, 1991;Hafner, 2003;Lindamer et al, 2003;Preston et al, 2002;Salokangas et al, 2003;Usall et al, 2003) but this has not been suffi ciently taken into account by the predictive scales available today (Phillips, 1953;Stephens et al, 1997;Strauss and Carpenter, 1974;Vaillant, 1964). Therefore, we have considered it important to examine whether the PRS had an equally promising predictive potential for both genders.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation